LEXICAL EXPRESSIVE MEANS AND STYLISTIC DEVICES (Ustozlar uchun, 2026)
This article discusses the role of lexical expressive means and stylistic devices in language. It explains how expressive vocabulary adds emotional and evaluative meaning, while stylistic devices are used deliberately to achieve specific effects in speech and writing. The paper also highlights different types of stylistic devices such as metaphor, irony, and repetition, and explains their functions. Special attention is given to their importance in language teaching and learning, especially for developing communicative competence. Understanding these concepts helps learners improve both comprehension and production skills.